The Competency of Elementary Physical Education Teachers in Implementing Learning with Integrative Thematic Approach - Parista, Vivi Septiana; Rumini, Rumini; Yudha Kusuma, Donny Wira (Journal of Physical Education and Sports, 2020)
This research aims to analyze the competence of Physical Education (PE) teachers in learning with an integrative thematic approach in Pekalongan District, reviewed from pedagogical competencies, professional competencies. This research was conducted through a qualitative approach with the design of ethnography using critical types of ethnography and data analysis conducted inductively with miles and huberman interactive cycles. The results showed that the pedagogical competencies of PE teachers have been able to: 1) master the characteristics of students, 2) develop curriculum, 3) utilize technology for learning, and 4) organize and utilize assessment and evaluation of processes and learning outcomes in learning with integrative thematic approach. While the professional competencies of teachers have been able to: 1) master the material, structure, concepts, and mindset of supporting science, 2) master basic competency and competency standards, and 3) develop learning materials creatively in the implementation of learning with an integrative thematic approach. There are teachers who have difficulty doing this, because they have never participated in Education and Training and age factors, so have not been able to adapt. It can be concluded that the pedagogical and professional competencies of PE elementary school teachers in Pekalongan District Session District are good enough in the implementation of learning with an integrative thematic approach.